Poverty and Serious Mental Illness: Toward Action on a Seemingly Intractable Problem. Issue 1 (15th December 2017) - Sylvestre, John; Notten, Geranda; Kerman, Nick; Polillo, Alexia; Czechowki, Konrad
Abstract: This paper examines the issue of poverty among people with serious mental illness (SMI), positioning it as a key issue to be confronted by community mental health systems and practitioners. The paper reviews three perspectives on poverty, considering how each sheds light on poverty among people with SMI, and their implications for action: (a) monetary resources, (b) basic needs, and (c) capabilities. The paper argues that community mental health programs and systems are currently unable to address poverty as they are overly focused on individual‐level interventions that, on their own, cannot raise people out of poverty. The paper calls for a social justice value, informed by the concept of citizenship, as a necessary complement to the recovery concept that has informed community mental health practice for almost 25 years. Finally, the paper argues that community psychologists, with their concepts, methods, and values, are well positioned to contribute to this important issue. However, it also contends that addressing poverty requires collaboration from community psychologists with researchers and practitioners from other fields and domains of expertise to begin to make progress. Highlights: An examination of three perspectives on poverty. Considers why community mental health has not addressed poverty among people with mental illness. Offers strategies for addressing poverty among people with mental illness.